Public health significance of companion animals in emergence and re-emergence of bacterial zoonoses - Goni, Mohammed Dauda; Muhammad, Ibrahim Jalo; Bitrus, Asinamai Athliamai; Jajere, Saleh Mohammed; Shah, Mian Khaqan; Aliyu, Abdulwahab; Goje, Mohammed (Journal of Advanced Veterinary and Animal Research, 2018)
Companion animals especially cats and dogs can provide a bridge for transmission of emerging bacterial diseases that are zoonotic in nature. Zoonotic diseases had posed numerous risk to ownership of companion animals by human either through direct or indirect contact especially in recent years where livestock species are being used as pets. Furthermore, companion animals could play a significant role in zoonosis as a potential reservoirs of various infections. These diseases have impacted greatly to the definition of new paradigms posed by emerging and re-emerging infectious diseases particularly relating to biosecurity policies and broadly to the protection of public health. Multi-sectorial collaboration for disease containment should be emphasized towards curtailing and managing health risks regarding infectious zoonotic diseases. http://doi.org/10.5455/javar.2018.e267